Ethical Implication of Genetic Gender Manipulation for Economic Recession - Monday, Osebor Ikechukwu; Esq, Stephen CC Chukwuma (Bangladesh Journal of Bioethics, 2019)
A recession is a significant decline in economic activities. The effects of economic recession include general economic decline, drop in the stock market and increase in unemployment. While some have argued that bilateral relationship among nations is an ethical response to problem of economic recession but it does not solve the problem. The paper suggests genetic gender determination. Genetic gender determination is an agent-based ethics. It involves the scientific manipulation of the fetus of a woman to determine the gender of her offspring. Ethical issues linked to genetic gender determination, unbalance sex ratio, manipulation of genome, and possible spread of infectious or communicable diseases. The paper concludes that the genetic gender determination would help to cushion the effects of economic recession.